A microcavity array-based 3D model system of the hematopoietic stem cell niche - Gottwald, Eric; Nies, Cordula; Wuchter, Patrick; Saffrich, Rainer; Truckenmüller, Roman; Giselbrecht, Stefan (Stem cell mobilization, 2019)
Despite huge advances in recent years, the interaction between hematopoietic stem and progenitor cells (HSPCs) and their niches in the bone marrow is still far from being fully understood. One reason is that hematopoiesis is a multi-step maturation process leading to HSPC heterogeneity. Subpopulations of HSPCs can be identified by clonogenic assays or in serial transplantation experiments in mice following sublethal irradiation, but it is very complex to reproduce or even maintain stem cell plasticity in vitro. Advanced model systems have been developed that allow to precisely control and analyze key components of the physiologic microenvironment for not only fundamental research purposes but, as a long-term goal, also for clinical applications. In this chapter, we describe our approach of building an artificial hematopoietic stem cell niche in the form of polymer film-based microcavities with a diameter of 300 μm and a depth of up to 300 μm and arranged in a 634-cavity array. The polymer films are provided with 3 μm pores and thus allow perfusion of the culture medium. The microcavity arrays can be inserted into a microbioreactor where a closed circulation loop can be tightly controlled with regard to medium flow and gas supply. The microcavity arrays were used for a three-dimensional (3D) co-culture of MSCs and HSPCs in a defined ratio over a time period of up to 21 days. With this setup, it could be demonstrated that the HSPCs maintained their stem cell characteristics more efficiently as compared to conventional monolayer co-culture controls.
Gesehen am 06.05.2020